Fair Play or Fair Pay? Gender Relations, Class Consciousness, and Union Solidarity in the Canadian UE - Guard, Julie (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1996)
Women who were activists in the Canadian district of the United Electrical, Radio and Machine Workers of America (UE) during the postwar and cold war era challenge the assumption that class consciousness is incompatible with female gender consciousness. Encouraged by the leadership's espoused commitment to gender equality, and secure in their strategic importance as a quarter of the UE's membership, women activists not only refused to accept second-class status within the union, but called, in the name of solidarity, for men's active support in the struggle for women's rights. Although their arguments for a gender-conscious analysis of class struggle failed to convince the UE's leadership, their struggle laid the foundation for the working-class feminism that later emerged within the union.